Sensitivity of Simulated Hyporheic Exchange to River Bathymetry: The Steinlach River Test Site. Issue 3 (22nd August 2018) - Chow, Reynold; Wu, Hao; Bennett, Jeremy P.; Dugge, Jürnjakob; Wöhling, Thomas; Nowak, Wolfgang
Abstract: This study determines the aspects of river bathymetry that have the greatest influence on the predictive biases when simulating hyporheic exchange. To investigate this, we build a highly parameterized HydroGeoSphere model of the Steinlach River Test Site in southwest Germany as a reference. This model is then modified with simpler bathymetries, evaluating the changes to hyporheic exchange fluxes and transit time distributions. Results indicate that simulating hyporheic exchange with a high‐resolution detailed bathymetry using a three‐dimensional fully coupled model leads to nested multiscale hyporheic exchange systems. A poorly resolved bathymetry will underestimate the small‐scale hyporheic exchange, biasing the simulated hyporheic exchange towards larger scales, thus leading to overestimates of hyporheic exchange residence times. This can lead to gross biases in the estimation of a catchment's capacity to attenuate pollutants when extrapolated to account for all meanders along an entire river within a watershed. The detailed river slope alone is not enough to accurately simulate the locations and magnitudes of losing and gaining river reaches. Thus, local bedforms in terms of bathymetric highs and lows within the river are required. Bathymetry surveying campaigns can be more effective by prioritizing bathymetry measurements along the thalweg and gegenweg of a meandering channel. We define the gegenweg as the line that connects the shallowest points in successive cross‐sections along a river opposite to the thalweg under average flow conditions. Incorporating local bedforms will likely capture the nested nature of hyporheic exchange, leading to more physically meaningful simulations of hyporheic exchange fluxes and transit times. Abstract : Article impact statement : Three‐dimensional fully coupled surface water‐groundwater models with detailed river bathymetry contrasts lead to nested multiscale hyporheic exchange systems.